Oxidized-LDL and Fe3+/Ascorbic Acid-Induced Oxidative Modifications and Phosphatidylserine Exposure in Human Platelets are Reduced by Melatonin - (:unkn) unknown (CHARLES UNIV PRAGUE, FIRST FACULTY MEDICINE, 2009)
Low-density lipoprotein (LDL) modifications and platelet activation are major risk factors for cardiovascular diseases. When platelets are exposed to oxidative stress, they become activated. Oxidized LDL (ox-LDL) and metal-catalysed oxidation systems such as Fe3+/ascorbic acid increase free radical production. We wanted to verify whether melatonin has a protective effect against oxidative modifications and phosphatidylserine externalization in platelets induced by ox-LDL and Fe3+/ascorbic acid. For in vitro effects of melatonin on platelets, ADP-activated platelets were incubated with ox-LDL or Fe3+/ascorbic acid for 1 h at 37 degrees C with or without melatonin. Then platelet malondialdehyde, protein carbonyl and glutathione levels were measured. Platelet phosphatidylserine exposure was measured with annexin-V using flow cytometry. Malondialdehyde, protein carbonyl and phosphatidylserine levels of platelets treated with Fe3+/ascorbic acid significantly increased compared to the control group. Glutathione contents of Fe3+/ascorbic acid-treated platelets significantly decreased. Melatonin pre-treatment of Fe3+/ascorbic acid-treated platelets caused a marked reduction in malondialdehyde anti phosphatidylserine levels and a marked increase in glutathione levels. Melatonin also caused non-significant reduction in protein carbonyl contents of Fe3+/ascorbic acid-treated platelets. Malondialdehyde, protein carbonyl and phosphatidylserine levels of platelets treated with ox-LDL also significantly increased compared to the control group. Platelet glutathione levels non-significantly decreased with ox-LDL. With addition of melatonin, malondialdehyde, protein carbonyl and phosphatidylserine levels of platelets treated with ox-LDL significantly decreased. These data suggest that melatonin May protect platelets from iron overload-induced and ox-LDL-induced oxidative modifications and also from the triggering signals of apoptosis activation, possibly due to its scavenger effect on toxic free radicals.
Keywords: melatonin; ox-LDL; oxidative modifications; iron; ascorbic acid; phosphatidylserine; platelet; HYDROXYL RADICAL FORMATION; LOW-DENSITY-LIPOPROTEIN; LIPID-PEROXIDATION; GLUTATHIONE DEPLETION; CELL-DEATH; APOPTOSIS; ACTIVATION; IRON; AGGREGATION; ABSENCE